TILED DISPLAY APPARATUS, TILED DISPLAY CONTROL METHOD, AND NON-TRANSITORY COMPUTER-READABLE STORAGE MEDIUM - ZHANG, Enliang; MENG, Zhankun; QI, Jiakun; YAN, Hengyu; SU, Junning; NIU, Hanzhang; LI, Shou (2022)
A tiled display apparatus includes a main display driving board and display modules. Each display module includes a system board. The main display driving board is coupled to a first stage system board. The main display driving board is configured to receive a display signal, acquire a main screen region display signal, and transmit the main screen region display signal to the first stage system board. The system board is configured to receive the main screen region display signal, and extract a group of main screen region display data corresponding thereto from the main screen region display signal to control a display module to which the system board belongs to display an image according to the main screen region display data. Except for a last stage system board, remaining system boards are each further configured to transmit the received main screen region display signal to a next stage system board.